Electrolyte, lithium ion battery containing electrolyte and electronic equipment

By using 1,3-dioxane compounds and polyboric acid compounds with specific structures in the electrolyte of lithium-ion batteries, the problem that existing electrolytes cannot take into account multiple performances is solved, and the efficient performance of the battery is achieved. stability.

CN119447447AActive Publication Date: 2025-02-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411659250.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The electrolyte in existing lithium-ion batteries cannot take into account high conductivity, high ion mobility, low viscosity, excellent chemical stability and electrochemical stability.

Method used

An electrolyte including 1,3-dioxane compounds and polyboric acid compounds having a specific structure is used, and the specific structure is shown in formula I and formula II-1/II-2.

Benefits of technology

The electrolyte has achieved high conductivity, high ion mobility coefficient, low viscosity, excellent chemical stability and electrochemical stability, resulting in a reduced impedance of lithium-ion batteries, a high recovery rate of high temperature capacity, a low volume expansion rate of high temperature, and a low volume expansion rate of high temperature. The expansion rate of the rear fully charged negative electrode sheet is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447447A_ABST
    Figure CN119447447A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte, a lithium ion battery containing the electrolyte and electronic equipment. The electrolyte comprises a 1, 3-dioxo heterocyclic compound and a polyboric acid compound; the structure of the 1, 3-dioxo heterocyclic compound is as shown in a formula I; the structure of the polyboric acid compound is as shown in a formula II-1 and / or a formula II-2. The electrolyte has high conductivity, high ion mobility coefficient, low viscosity and excellent chemical stability and electrochemical stability, the lithium ion battery containing the electrolyte has low impedance, high high-temperature capacity recovery rate and low high-temperature volume expansion rate, and the expansion rate of a fully-charged negative plate after formation is low. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrolyte and a lithium ion battery and electronic equipment containing the electrolyte. Background Art

[0002] With the improvement of global environmental awareness, new energy vehicles are rapidly becoming the first choice to replace traditional fuel vehicles. In recent years, electric vehicles have become more and more common in people's homes, greatly facilitating everyone's daily travel. At the same time, due to many defects such as short driving range and low energy density, the promotion and popularization of electric vehicles has been limited to a certain extent. Fast charging technology has become a key innovation to solve this bottleneck of insufficient driving range. Compared with traditional charging methods, fast charging technology significantly shortens the charging time, meets users' needs for convenient and efficient charging, and further promotes the promotion and development of new energy vehicles.

[0003] As more and more consumers favor new energy vehicles with higher energy density and longer driving range, the development and application of negative electrode materials with higher silicon content have been greatly promoted. Due to the volume expansion of silicon material particles, the electrode structure is broken and the active material peels off. The resulting fresh interface has strong electrochemical reducibility. The carbonate solvent system in the electrolyte is reduced to a certain extent to produce gas. The interfacial side reactions caused by the volume expansion of these silicon materials will lead to higher capacity loss. Therefore, it is urgent to develop a solvent with high conductivity, high ion migration coefficient, low viscosity, and high chemical stability and electrochemical stability. Summary of the invention

[0004] In order to solve the defect that the electrolyte in the existing lithium-ion battery cannot take into account high conductivity, high ion mobility coefficient, low viscosity and excellent chemical stability and electrochemical stability, the present invention provides an electrolyte and a lithium-ion battery and electronic equipment containing the electrolyte. The electrolyte has high conductivity, high ion mobility coefficient, low viscosity and excellent chemical stability and electrochemical stability. The lithium-ion battery containing the electrolyte has low impedance, high high-temperature capacity recovery rate, low high-temperature volume expansion rate, and low expansion rate of the fully charged negative electrode sheet after formation.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions.

[0006] In a first aspect, the present invention provides an electrolyte, the electrolyte comprising a 1,3-dioxocyclic compound and a polyboric acid compound; the structure of the 1,3-dioxocyclic compound is as shown in Formula I; the structure of the polyboric acid compound is as shown in Formula II-1 and / or Formula II-2;

[0007] ;

[0008] Wherein, in Formula I, n is selected from an integer within the range of 1 to 4; in Formula II-1 and Formula II-2, n2 is each independently selected from an integer within the range of 1 to 12; in Formula II-2, n3 is selected from an integer within the range of 1 to 3;

[0009] R' in formula II-1 is selected from one or more of hydrogen, alkyl having 1 to 10 carbon atoms, cyclic alkyl, alkenyl, cyclic alkenyl, alkynyl, cyclic alkynyl, haloalkyl, haloalkenyl, haloalkynyl, aryl having 6 to 10 carbon atoms, and benzyl;

[0010] M in formula II-2 is selected from one or more of Li, Be, Na, Mg, K, Ca, Mn, Fe, Co, Ni, Cu and Zn.

[0011] In a second aspect, the present invention provides a lithium ion battery comprising the electrolyte as described above.

[0012] In a third aspect, the present invention provides an electronic device comprising the lithium-ion battery as described above.

[0013] The positive and progressive effects of the present invention are:

[0014] The present invention aims at the problem that the electrolyte in lithium-ion batteries cannot have high conductivity, high ion mobility coefficient, low viscosity and excellent chemical stability and electrochemical stability. The electrolyte includes 1,3-dioxocyclic compounds with the structure of formula I and polyboric acid compounds with the structure of formula II. The electrolyte has high conductivity, high ion mobility coefficient, low viscosity and excellent chemical stability and electrochemical stability. The lithium-ion battery containing the electrolyte has low impedance, high high-temperature capacity recovery rate, low high-temperature volume expansion rate, and low expansion rate of the fully charged negative electrode sheet after formation. DETAILED DESCRIPTION

[0015] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0016] Electrolyte

[0017] In the electrolyte provided in the first aspect of the present invention, the electrolyte comprises a 1,3-dioxocyclic compound and a polyboric acid compound; the structure of the 1,3-dioxocyclic compound is as shown in Formula I; the structure of the polyboric acid compound is as shown in Formula II-1 and / or Formula II-2;

[0018] ;

[0019] Wherein, in Formula I, n is selected from an integer within the range of 1 to 4; in Formula II-1 and Formula II-2, n2 is each independently selected from an integer within the range of 1 to 12; in Formula II-2, n3 is selected from an integer within the range of 1 to 3;

[0020] R' in formula II-1 is selected from one or more of hydrogen, alkyl having 1 to 10 carbon atoms, cyclic alkyl, alkenyl, cyclic alkenyl, alkynyl, cyclic alkynyl, haloalkyl, haloalkenyl, haloalkynyl, aryl having 6 to 10 carbon atoms, and benzyl;

[0021] M in formula II-2 is selected from one or more of Li, Be, Na, Mg, K, Ca, Mn, Fe, Co, Ni, Cu and Zn.

[0022] In some preferred embodiments, the 1,3-dioxacyclic compound is selected from one or more of compounds ac:

[0023] .

[0024] In some preferred embodiments, in formula II-2, when M is one or more of Li, Na and K, n3 is 1; when M is one or more of Be, Mg, Ca, Cu and Zn, n3 is 2; when M is one or more of Mn, Fe, Co and Ni, n3 is 2 or 3.

[0025] In some preferred embodiments, the polyboric acid compound is selected from one or more of compounds dg:

[0026] .

[0027] In some optional embodiments, the content of the 1,3-dioxocyclic compound is 0.05% to 20%, preferably 0.5% to 10%, for example 3%, 6%, 8% or 15%, where the percentage is the mass percentage of the electrolyte.

[0028] In some optional embodiments, the content of the polyboric acid compound is 0.05% to 6%, preferably 0.5% to 6%, for example 1%, where the percentage is the mass percentage of the electrolyte.

[0029] In some optional embodiments, the mass ratio of the 1,3-dioxacyclic compound to the polyboric acid compound is (0.05-120):1, preferably (1-60):1, for example, 6:1, 12:1, 15:1 or 20:1.

[0030] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 6%, and the content of compound d is, for example, 1%.

[0031] In a specific embodiment, the electrolyte includes compound a, compound b and compound d; the content of compound a is, for example, 3%, the content of compound b is, for example, 3%, and the content of compound d is, for example, 1%.

[0032] In a specific embodiment, the electrolyte includes compound a, compound c and compound e; the content of compound a is, for example, 3%, the content of compound c is, for example, 3%, and the content of compound e is, for example, 1%.

[0033] In a specific embodiment, the electrolyte includes compound a, compound c, compound e and compound f; the content of compound a is, for example, 3%, the content of compound c is, for example, 3%, the content of compound e is, for example, 1%, and the content of compound f is, for example, 2%.

[0034] In a specific embodiment, the electrolyte includes compound a, compound c, compound e and compound f; the content of compound a is, for example, 3%, the content of compound c is, for example, 3%, the content of compound e is, for example, 3%, and the content of compound f is, for example, 3%.

[0035] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 3%, and the content of compound d is, for example, 1%.

[0036] In a specific embodiment, the electrolyte includes compound a, compound d, compound e and compound f; the content of compound a is, for example, 3%, the content of compound d is, for example, 1%, the content of compound e is, for example, 1%, and the content of compound f is, for example, 1%.

[0037] In a specific embodiment, the electrolyte includes compound b, compound c, compound d, compound e and compound f; the content of compound b is, for example, 3%, the content of compound c is, for example, 3%, the content of compound d is, for example, 1%, the content of compound f is, for example, 1%, and the content of compound e is, for example, 1%.

[0038] In a specific embodiment, the electrolyte includes compound c and compound d; the content of compound c is, for example, 8%, and the content of compound d is, for example, 1%.

[0039] In a specific embodiment, the electrolyte includes compound c and compound e; the content of compound c is, for example, 6%, and the content of compound e is, for example, 0.5%.

[0040] In a specific embodiment, the electrolyte includes compound c and compound e; the content of compound c is, for example, 6%, and the content of compound e is, for example, 0.1%.

[0041] In a specific embodiment, the electrolyte includes compound c and compound f; the content of compound c is, for example, 6%, and the content of compound f is, for example, 0.5%.

[0042] In a specific embodiment, the electrolyte includes compound c, compound d and compound f; the content of compound c is, for example, 6%, the content of compound d is, for example, 3%, and the content of compound f is, for example, 3%.

[0043] In a specific embodiment, the electrolyte includes compound a, compound c and compound f; the content of compound a is, for example, 3%, the content of compound c is, for example, 3%, and the content of compound f is, for example, 0.5%.

[0044] In a specific embodiment, the electrolyte includes compound a, compound c and compound e; the content of compound a is, for example, 3%, the content of compound c is, for example, 3%, and the content of compound e is, for example, 6%.

[0045] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 0.05%, and the content of compound d is, for example, 1%.

[0046] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 10%, and the content of compound d is, for example, 1%.

[0047] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 15%, and the content of compound d is, for example, 1%.

[0048] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 20%, and the content of compound d is, for example, 1%.

[0049] In a specific embodiment, the electrolyte includes compound a and compound d; the content of compound a is, for example, 6%, and the content of compound d is, for example, 0.05%.

[0050] In the present invention, the solvent in the electrolyte may be a solvent conventionally used in the art, and may generally include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate, fluoroethylene carbonate, trifluoroethyl methyl carbonate, trifluoropropylene carbonate, trifluoromethylpropylene, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0051] In some preferred embodiments, the solvent in the electrolyte includes one or more of cyclic carbonates, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), trifluoroethyl methyl carbonate, trifluoropropylene carbonate, trifluoromethyl propylene, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; wherein the cyclic carbonate is preferably ethylene carbonate (EC) and / or propylene carbonate (PC).

[0052] In some optional embodiments, the additive in the electrolyte includes one or both of fluoroethylene carbonate (FEC) and lithium bis(oxalatoborate) (LiBOB).

[0053] In the present invention, the lithium salt in the electrolyte may be a lithium salt conventionally used in the art, and may generally include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0054] In some preferred embodiments, the lithium salt in the electrolyte includes one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

[0055] In some optional embodiments, the electrolyte includes cyclic carbonate and fluoroethylene carbonate, and the electrolyte satisfies the following conditions:

[0056] 1≤Y1 / (Y2+Y3)≤40;

[0057] 0.05≤Y2 / Y3≤70;

[0058] 0.1%≤Y1≤35%;

[0059] 0.1%≤Y2≤35%;

[0060] Wherein, the cyclic carbonate is ethylene carbonate and / or propylene carbonate, Y1 is the mass percentage of the cyclic carbonate in the electrolyte, Y2 is the mass percentage of the fluoroethylene carbonate in the electrolyte, and Y3 is the mass percentage of the 1,3-dioxocyclic compound in the electrolyte.

[0061] In some preferred embodiments, 0.5≤Y2 / Y3≤12.

[0062] Lithium-ion battery

[0063] The lithium ion battery provided in the second aspect of the present invention comprises the electrolyte as described above.

[0064] In the present invention, the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator.

[0065] Positive electrode

[0066] In the present invention, the positive electrode sheet in the lithium-ion battery includes a positive electrode current collector, and the positive electrode material layer is arranged on at least one surface of the positive electrode current collector.

[0067] In the present invention, the positive electrode active material in the lithium ion battery can be a positive electrode active material conventionally used in the art, generally selected from lithium transition metal oxides and modified compounds thereof; wherein the lithium transition metal oxide preferably includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide; wherein the content of manganese element in the positive electrode active material in the lithium ion battery is preferably >0.5%, and the percentage is the molar ratio of the total molar number of metal elements other than lithium in the positive electrode active material.

[0068] In some optional embodiments, the positive electrode active material in the lithium-ion battery is one or more of manganese iron lithium compounds, iron lithium compounds and manganese lithium compounds, preferably one or more of lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium iron manganese phosphate and lithium nickel manganese cobalt oxide.

[0069] In some optional embodiments, the content of manganese in the positive electrode active material in the lithium ion battery is greater than 10%, where the percentage is the molar ratio to the total molar number of metal elements other than lithium in the positive electrode active material.

[0070] In some preferred embodiments, the positive electrode active material in the lithium ion battery is selected from LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Mn 1.5 O4、LiFe 0.4 Mn 0.6 One or more of PO4 and LiFeMnPO4.

[0071] In some optional embodiments, the content of the positive electrode active material is greater than 90%, for example, 97%, where the percentage is the percentage of the total mass of the positive electrode material layer.

[0072] In some optional embodiments, the positive electrode material layer further includes a binder.

[0073] Among them, the type of the binder is not particularly limited, and can be selected from polyvinylidene fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, styrene-butadiene rubber (SBR), fluororubber and one or more of fluorine-containing acrylate resins, such as PVDF.

[0074] In some optional embodiments, the content of the binder is 1%-10%, where the percentage is the percentage of the total mass of the positive electrode material layer.

[0075] In some optional embodiments, the positive electrode material layer further includes a conductive agent.

[0076] The type of the conductive agent is not particularly limited, and is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black SP, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.

[0077] In a specific embodiment, the conductive agent is acetylene black.

[0078] In some optional embodiments, the content of the conductive agent is 0.2%-3%, for example, 2%, where the percentage is the percentage of the total mass of the positive electrode material layer.

[0079] In some specific embodiments, in the positive electrode material layer, the mass ratio of the positive electrode active material, the conductive agent and the binder is 97:2:1.

[0080] In the present invention, the positive electrode current collector may be a conventional positive electrode current collector in the art. The positive electrode current collector, as a substrate supporting the positive electrode material layer, may be a metal foil or a composite current collector. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system.

[0081] In some preferred embodiments, the metal foil is preferably aluminum foil or aluminum alloy.

[0082] In some preferred embodiments, the composite current collector includes a polymer material base and a metal layer formed on at least one surface of the polymer material base; the composite current collector can be obtained by compounding a metal material on a polymer material. Among them, the metal material preferably includes one or more of aluminum, aluminum alloy, nickel, nickel alloy, silver-based silver alloy and titanium alloy; the polymer material substrate preferably includes one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0083] Generally, the positive electrode current collector is aluminum foil.

[0084] In some embodiments, the preparation method of the positive electrode sheet includes: fully stirring and mixing the components of the positive electrode material layer in a solvent to obtain a positive electrode slurry, coating it on at least one surface of the positive electrode collector, drying, cold pressing, trimming, cutting, and slitting.

[0085] In some optional embodiments, the solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl carbonate, ethylene carbonate and diethylene carbonate, for example, NMP.

[0086] Negative plate

[0087] In the present invention, the negative electrode sheet in the lithium-ion battery comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector.

[0088] In the present invention, the negative electrode active material in the lithium-ion battery can be a conventional negative electrode active material in the art, preferably including one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. Among them, the silicon-based material preferably includes one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys; the tin-based material preferably includes one or more of elemental tin, tin-oxygen compounds and tin alloys.

[0089] In some optional embodiments, the negative electrode active material in the lithium ion battery is selected from graphite and / or silicon material; wherein the graphite preferably includes artificial graphite and / or natural graphite; the silicon material preferably includes silicon oxygen material and / or silicon carbon material; the content of Si element in the silicon material is preferably ≥10%, and the percentage is the mass percentage of the silicon material.

[0090] In some preferred embodiments, the negative electrode active material in the lithium ion battery includes a silicon material, the electrolyte includes fluoroethylene carbonate, and the electrolyte meets the following conditions:

[0091] 0.1≤(Y2+Y3) / Z1≤1;

[0092] 0.1%≤Z1≤30%;

[0093] 0.1%≤Y2≤30%;

[0094] Wherein, Z1 is the mass percentage of the silicon material in the negative electrode active material; Y2 is the mass percentage of the fluoroethylene carbonate in the electrolyte; and Y3 is the mass percentage of the 1,3-dioxocyclic compound in the electrolyte.

[0095] In a specific embodiment, the negative electrode active material is a silicon-carbon composite and artificial graphite.

[0096] In some embodiments, the negative electrode material layer further includes a thickener.

[0097] The addition of the thickener can increase the system viscosity of each component in the negative electrode slurry, and can be a thickener conventionally used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).

[0098] In some embodiments, the negative electrode material layer further includes a conductive agent.

[0099] There are no particular restrictions on the conductive agent, as long as it has conductivity and does not cause chemical changes in the battery. For example, the conductive agent may be: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black (Super P), acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.

[0100] In a specific embodiment, the conductive agent is conductive carbon black.

[0101] In some embodiments, the negative electrode material layer further includes a binder.

[0102] The type of the binder is not particularly limited, and can be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), lithium polyacrylate (PAALi), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as PAALi, PAA or SBR.

[0103] In some specific embodiments, in the negative electrode material layer, the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener is 96:2:1:1.

[0104] In the present invention, the negative electrode current collector may be a conventional negative electrode current collector in the art. The negative electrode current collector, as a substrate supporting the negative electrode material layer, may be a metal foil or a composite current collector. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system.

[0105] In some preferred embodiments, the metal foil is preferably copper foil.

[0106] In some preferred embodiments, the composite current collector includes a polymer material base and a metal layer formed on at least one surface of the polymer material base; the composite current collector can be obtained by compounding a metal material on a polymer material. Among them, the metal material preferably includes one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy; the polymer material substrate preferably includes one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0107] Generally, the negative electrode current collector is copper foil.

[0108] In some embodiments, the method for preparing the negative electrode sheet includes the following steps: thoroughly stirring and mixing the components of the negative electrode material layer in a solvent to obtain a negative electrode slurry, coating it on at least one surface of the negative electrode collector, drying, cold pressing, trimming, cutting, and slitting.

[0109] Diaphragm

[0110] In the present invention, the separator in the lithium-ion battery can be a separator conventionally used in the art. The separator can be a single-layer membrane or a multi-layer composite membrane. There is no particular restriction on the type of separator, and its material includes one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. Wherein, when the separator is a multi-layer composite membrane, the materials of each layer can be the same or different.

[0111] In some optional embodiments, the separator may be made of polypropylene film or polyethylene film.

[0112] Wherein, the air permeability of the diaphragm may be 180-380 s / 100mL.

[0113] Wherein, the porosity of the diaphragm may be 30%-50%.

[0114] The thickness of the diaphragm may be 5-40 μm, preferably 7-16 μm.

[0115] In a specific embodiment, the diaphragm is a polyethylene film; the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.

[0116] In the present invention, the preparation method of the lithium ion can adopt a conventional preparation method in the art, generally including using a winding process or a lamination process to make a positive electrode sheet, a separator and a negative electrode sheet into an electrode assembly.

[0117] In some embodiments, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence; then wrapping with an aluminum-plastic film to obtain a dry battery cell, injecting the electrolyte after drying, and finally preparing a soft-pack battery through packaging, standing, and formation.

[0118] Electronic devices

[0119] The electronic device provided in the third aspect of the present invention comprises the lithium-ion battery as described above.

[0120] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.

[0121] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention. The present invention is further illustrated by way of examples below, but the present invention is not limited to the scope of the embodiments described. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications. Unless otherwise specified, the reagents and raw materials used in the present invention are commercially available.

[0122] Example 1

[0123] (1) Preparation of electrolyte:

[0124] In an argon atmosphere glove box with a water content of <1ppm, EC, PC, EMC, and DEC are mixed at a mass ratio of 10:20:60:10 to obtain a mixed solvent. Lithium hexafluorophosphate (content 10%) and lithium bis(fluorosulfonyl)imide (content 6%) are dissolved in the mixed solvent. Compound I (compound a, content 6%) and compound II (compound d, content 1%) are added thereto and mixed evenly to obtain an electrolyte.

[0125] (2) Preparation of positive electrode:

[0126] The positive electrode active material lithium nickel manganese cobalt oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent acetylene black, and binder polyvinylidene fluoride are mixed in a mass ratio of 97:2:1 (a total of 100 parts by mass) and dissolved in a solvent NMP to form a positive electrode slurry. The positive electrode slurry is then coated on the current collector aluminum foil, and after drying, cold pressing, trimming, cutting, and striping are performed to obtain a positive electrode sheet.

[0127] (3) Preparation of negative electrode sheet:

[0128] The negative electrode active material (silicon-carbon composite and artificial graphite, the mass percentage of silicon-carbon composite in the negative electrode active material is 12%, wherein the silicon element in the silicon-carbon composite: carbon element = 1:1), conductive carbon black, thickener CMC, binder PAALi are mixed in a mass ratio of 96:2:1:1 (a total of 100 parts by mass), added to the solvent deionized water, and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry (the solid content of the slurry is controlled between 45% and 50%). Then the negative electrode slurry is coated on the current collector copper foil, and after drying, cold pressing, trimming, cutting, and striping are performed to obtain a negative electrode sheet.

[0129] (4) Preparation of lithium-ion batteries:

[0130] The prepared positive electrode sheet, separator and negative electrode sheet are stacked in sequence and loaded into an aluminum-plastic film to obtain a dry battery cell, and the dry battery cell is dried at 80°C. After the electrolyte is injected into the dry battery cell and sealed, it is placed at a high temperature of 45°C for 36 hours. After being taken out, it is charged in steps at 45°C under normal pressure, first charged to 3.05V with 0.02C, and then charged to 3.4V with 0.05C current; some of the batteries used for the expansion rate test of the negative electrode sheet are charged to 3.75V with 0.33C (full charge); after aging and capacity division, it is obtained. Among them, the separator is a polyethylene film, the thickness of the separator is 11μm, the air permeability of the separator is 230s / 100mL, and the porosity of the separator is 40%.

[0131] Example 2

[0132] The only difference between Example 2 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound b (content is 3%); the compound of formula II is compound d (content is 1%), and the other conditions are the same as those in Example 1.

[0133] Example 3

[0134] The only difference between Example 3 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound c (content is 3%); the compound of formula II is compound e (content is 1%), and the other conditions are the same as those in Example 1.

[0135] Example 4

[0136] The only difference between Example 4 and Example 2 is that in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, lithium bis(fluorosulfonyl)imide is not used, and the other conditions are the same as those in Example 2.

[0137] Example 5

[0138] The only difference between Example 5 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound b (content is 3%) and compound c (content is 3%); the compound of formula II is compound f (content is 1%), and the other conditions are the same as in Example 1.

[0139] Example 6

[0140] The only difference between Example 6 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound c (content is 3%); the compound of formula II is compound e (content is 1%) and compound f (content is 2%), and the other conditions are the same as in Example 1.

[0141] Example 7

[0142] The only difference between Example 7 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound c (content is 3%); the compound of formula II is compound e (content is 3%) and compound f (content is 3%), and the other conditions are the same as in Example 1.

[0143] Example 8

[0144] The only difference between Example 8 and Example 4 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound c (content is 3%); the compound of formula II is compound f (content is 1%), and the other conditions are the same as those in Example 4.

[0145] Example 9

[0146] The only difference between Example 9 and Example 1 is that in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the content of compound a is 3%, and the other conditions are the same as those in Example 1.

[0147] Example 10

[0148] The only difference between Example 10 and Example 1 is that in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound a (content is 3%); the compound of formula II is compound d (content is 1%), compound e (content is 1%) and compound f (content is 1%), and the other conditions are the same as in Example 1.

[0149] Embodiment 11

[0150] The only difference between Example 11 and Example 1 is that: in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound b (content is 3%) and compound c (content is 3%); the compound of formula II is compound d (content is 1%), compound e (content is 1%) and compound f (content is 1%), and the other conditions are the same as in Example 1.

[0151] Example 12

[0152] The only difference between Example 12 and Example 1 is that in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound c (content is 8%); the compound of formula II is compound d (content is 1%), and the other conditions are the same as in Example 1.

[0153] Embodiment 13

[0154] The only difference between Example 13 and Example 1 is that in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound c (content is 6%); the compound of formula II is compound e (content is 0.5%), and the other conditions are the same as in Example 1.

[0155] Embodiment 14

[0156] The only difference between Example 14 and Example 1 is that: in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound c (content is 6%); the compound of formula II is compound e (content is 0.1%), and the other conditions are the same as in Example 1.

[0157] Embodiment 15

[0158] The only difference between Example 15 and Example 1 is that in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound c (content is 6%); the compound of formula II is compound f (content is 0.5%), and the other conditions are the same as in Example 1.

[0159] Example 16

[0160] The only difference between Example 16 and Example 1 is that: in the preparation of the electrolyte, the content of lithium hexafluorophosphate is 14.9%, and lithium bis(fluorosulfonyl)imide is not used; the compound of formula I is compound c (content is 6%); the compound of formula II is compound d (content is 3%) and compound f (content is 3%), and the other conditions are the same as in Example 1.

[0161] Embodiment 17

[0162] The only difference between Example 17 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound c (content is 3%); the compound of formula II is compound f (content is 0.5%), and the other conditions are the same as in Example 1.

[0163] Embodiment 18

[0164] The only difference between Example 18 and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%) and compound c (content is 3%); the compound of formula II is compound e (content is 6%), and the other conditions are the same as in Example 1.

[0165] Embodiment 19

[0166] The only difference between Example 19 and Example 1 is that in the preparation of the electrolyte, the content of compound a is 0.05%, and the other conditions are the same as those in Example 1.

[0167] Embodiment 20

[0168] The only difference between Example 20 and Example 1 is that in the preparation of the electrolyte, the content of compound a is 10%, and the other conditions are the same as those in Example 1.

[0169] Embodiment 21

[0170] The only difference between Example 21 and Example 1 is that in the preparation of the electrolyte, the content of compound a is 15%, and the other conditions are the same as those of Example 1.

[0171] Embodiment 22

[0172] The only difference between Example 22 and Example 1 is that in the preparation of the electrolyte, the content of compound a is 20%, and the other conditions are the same as those of Example 1.

[0173] Embodiment 23

[0174] The only difference between Example 23 and Example 1 is that in the preparation of the electrolyte, the content of compound d is 0.05%, and the other conditions are the same as those of Example 1.

[0175] Embodiment 24

[0176] The difference between Example 24 and Example 1 is that the positive electrode active material is a manganese iron lithium compound (LiFe 0.4 Mn 0.6 PO4), and the other conditions were the same as in Example 1.

[0177] Embodiment 25

[0178] The only difference between Example 25 and Example 1 is that in the preparation of the electrolyte, when adding the compound of Formula I and the compound of Formula II, LiBOB (content of 1%) is also added, and the other conditions are the same as those of Example 1.

[0179] Embodiment 26

[0180] The only difference between Example 26 and Example 1 is that in the preparation of the electrolyte, when adding the compound of formula I and the compound of formula II, FEC (content of 3%) is also added, and the other conditions are the same as those in Example 1.

[0181] Embodiment 27

[0182] The only difference between Example 27 and Example 1 is that in the preparation of the electrolyte, when adding the compound of Formula I and the compound of Formula II, LiBOB (content of 1%) and FEC (content of 3%) are also added, and the other conditions are the same as those in Example 1.

[0183] Comparative Example 1

[0184] The difference between this comparative example and Example 1 is that in the preparation of the electrolyte, FEC (content of 6%) is used to replace the compound of formula I and the compound of formula II, and the other conditions are the same as those in Example 1.

[0185] Comparative Example 2

[0186] The difference between this comparative example and Example 4 is that in the preparation of the electrolyte, FEC (content of 6%) is used to replace the compound of formula I and the compound of formula II, and the other conditions are the same as those in Example 1.

[0187] Comparative Example 3

[0188] The difference between this comparative example and Example 1 is that in the preparation of the electrolyte, FEC (content of 3%) is used to replace the compound of formula I and the compound of formula II, and the other conditions are the same as those in Example 1.

[0189] Comparative Example 4

[0190] The difference between this comparative example and Example 4 is that in the preparation of the electrolyte, FEC (content of 3%) is used to replace the compound of formula I and the compound of formula II, and the other conditions are the same as those in Example 1.

[0191] Comparative Example 5

[0192] The difference between this comparative example and Example 4 is that in the preparation of the electrolyte, FEC (content of 6%) and LiBOB (content of 1%) are used to replace the compound of formula I and the compound of formula II, and the other conditions are the same as those in Example 1.

[0193] Comparative Example 6

[0194] The only difference between this comparative example and Example 1 is that in the preparation of the electrolyte, the compound of formula I is compound a (content is 3%); FEC (content is 3%) is used to replace the compound of formula II, and the other conditions are the same as those in Example 1.

[0195] Comparative Example 7

[0196] The difference between this comparative example and Example 1 is that no compound of formula II is used in the preparation of the electrolyte, and the other conditions are the same as those in Example 1.

[0197] Comparative Example 8

[0198] The difference between this comparative example and Example 4 is that in the preparation of the electrolyte, there is no compound of formula II, and the compounds of formula I are compound a (content of 3%) and compound b (content of 3%), and the other conditions are the same as those in Example 1.

[0199] Comparative Example 9

[0200] The difference between this comparative example and Example 1 is that in the preparation of the electrolyte, LiBOB (content of 1%) is used to replace the compound of formula II, and the other conditions are the same as those in Example 1.

[0201] Comparative Example 10

[0202] The difference between this comparative example and Example 4 is that in the preparation of the electrolyte, the compound of formula I is compound c (content is 3%) and compound b (content is 3%), LiBOB (content is 1%) is used to replace the compound of formula II, and the other conditions are the same as those in Example 1.

[0203] Comparative Example 11

[0204] The only difference between this comparative example and Example 16 is that no compound of formula I is used in the preparation of the electrolyte, and the other conditions are the same as those in Example 16.

[0205] Comparative Example 12

[0206] The only difference between this comparative example and Example 18 is that no compound of formula I is used in the preparation of the electrolyte, and the other conditions are the same as those in Example 18.

[0207] The contents of components other than the solvent in the electrolytes obtained in the above Examples 1-27 and Comparative Examples 1-12 are shown in Table 1.

[0208] Effect Example 1

[0209] The lithium ion batteries prepared in Examples 1-27 and Comparative Examples 1-12 were subjected to the following performance tests:

[0210] (1) Low temperature DCR

[0211] At 25°C, charge the lithium-ion battery at a constant current of 1 / 3C to 4.25V, and then charge it at a constant voltage to a current of 0.05C. Then discharge the battery at a constant current of 1 / 3C to 2.8V. Repeat the above charging steps and record the charging capacity as C0. Discharge the battery at a constant current of 1 / 3C to (50%×C0). Then place the battery at -20°C and record the initial voltage as U0. Discharge the battery at a constant current of 1C for 30s and record the terminal voltage as U1.

[0212] At -20℃, DCR=(U0-U1) / (C0×1).

[0213] (2)Normal temperature DCR

[0214] At 25°C, charge the lithium-ion battery at 1 / 3C constant current to 4.25V, then charge at constant voltage to a current of 0.05C. Then discharge the battery at 1 / 3C constant current to 2.8V. Repeat the above charging steps and record the charging capacity as C1. Discharge the battery at 1 / 3C constant current to (50%×C1), record the initial voltage as U2. Discharge the battery at 1C constant current for 30s, record the terminal voltage as V3.

[0215] DCR=(U2-U3) / (C1×1) at 25℃.

[0216] (3) High temperature storage performance

[0217] After fully charging the battery to 4.25V at 25°C, discharge it to 2.8V at a rate of 0.33C, and record the discharge capacity as C2. After storing the lithium-ion battery at 60°C for 30 days, first discharge it to 2.8V at 1 / 3C constant current at 25°C, then charge it to 4.25V at 1 / 3C constant current, then charge it to 0.05C at constant voltage, and then discharge it to 2.8V at 1 / 3C constant current, and record the discharge capacity as C3.

[0218] ① The capacity recovery rate after storage at 60°C for 30 days is (C3 / C2)×100%.

[0219] Repeat the above charging steps and record the charging capacity as C4. Discharge the battery at a constant current of 1 / 3C to (50%×C4), and record the initial voltage as U4. Discharge the battery at a constant current of 1C for 30s, and record the terminal voltage as U5.

[0220] ② At 60℃, DCR=(U4-U5) / (C4×1).

[0221] ③ The DCR growth rate after storage at 60°C for 30 days is (DCR after storage for 30 days - initial DCR) / initial DCR×100%.

[0222] The volume V1 of the lithium ion battery at 25°C before storage at 60°C and the volume V2 at room temperature after storage at 60°C for 30 days were recorded.

[0223] ④ Storage at 60℃ for 30 days: Volume expansion rate = (V2-V1) / V1×100%.

[0224] (4) Expansion rate of negative electrode after formation

[0225] The expansion rate of the negative electrode sheet after formation = (the thickness of the fully charged negative electrode sheet after formation - the thickness of the negative electrode sheet in the dry battery cell after drying) / the thickness of the negative electrode sheet in the dry battery cell after drying × 100%.

[0226] The above test results are shown in Table 2.

[0227]

[0228]

[0229] Note: “ / ” in Table 1 means that the condition parameter is not involved in the specific experiment.

[0230] As can be seen from Table 1 and Table 2, the electrolyte of the present invention uses a 1,3-dioxocyclic compound (compound of formula I) and a polyboric acid compound (compound of formula II) with a specific structure. The electrolyte has high conductivity, high ion mobility coefficient, low viscosity, and excellent chemical stability and electrochemical stability. The lithium-ion battery containing the electrolyte has low impedance, high high-temperature capacity recovery rate, low high-temperature volume expansion rate, and low expansion rate of the fully charged negative electrode sheet after formation.

[0231] In Example 1-27 of the present invention, 1,3-dioxocyclic compounds and polyboric acid compounds are added to the electrolyte to achieve excellent chemical stability and electrochemical stability. The DCR growth rate of the lithium-ion battery containing it can be lower than 40%, or even lower than 20% when stored at 60°C for 30 days; the volume expansion rate can be lower than 30%, or even lower than 15% when stored at 60°C for 30 days. On this basis, the DCR can be lower than 350 mΩ at -20°C, the DCR can be lower than 100 mΩ at 25°C, the capacity recovery rate can be as high as 94% or more when stored at 60°C for 30 days; the expansion rate of the fully charged negative electrode sheet after formation can be lower than 10%.

[0232] In the present invention, when the compound of formula I or formula Ⅱ with a specific structure is used alone in the electrolyte, even with additives such as FEC or LIBOB, the above-mentioned excellent effects cannot be achieved. Only when the two work together can the above-mentioned effects be achieved. This may be because the compound of formula I has better high temperature stability and fewer interfacial side reactions, which is beneficial to improving the cycle dynamics and significantly improving the cycle life; and its electrochemical reactivity is low, the side reaction gas production is lower, and the electron gain and loss at the interface are effectively reduced. At the same time, the compound of formula I can also form a dense mesh SEI film on the negative electrode with more serious volume expansion, especially the silicon negative electrode. It has high toughness and density, and can effectively inhibit the volume expansion of the negative electrode sheet after formation. At the same time, the interface film formed on the silicon particles can make up for the defects such as active lithium loss and low first efficiency caused by the silicon material. Compared with the sintering coating of the silicon material surface, the cost brought by its performance improvement will also be lower; and the compound of formula Ⅰ is easier to form an inorganic layer interface film rich in electron-deficient on the positive electrode side, which is easy to attract the electron-rich compound of formula Ⅱ, so that it is easier to form a double ion layer with higher charge density at the interface, which helps to further reduce the interface polarization and is more conducive to the dynamics of lithium ion deintercalation.

[0233] Compared with Example 1, FEC was added to the electrolyte of Comparative Examples 1 and 3, but the compound of Formula I and the compound of Formula II were not added. The DCR growth rate of the lithium-ion battery containing it at 60°C for 30 days, the DCR at -20°C and the DCR at 25°C were greatly improved, the volume expansion rate at 60°C for 30 days and the capacity recovery rate at 60°C for 30 days were significantly deteriorated, and the expansion rate of the fully charged negative electrode sheet after formation was also significantly improved. Similarly, compared with Example 4, only FEC was added to the electrolyte of Comparative Examples 2 and 4, but the compound of Formula I and the compound of Formula II were not added, and the above performances were significantly deteriorated. Even if LiBOB was added to the electrolyte of Comparative Example 5 on the basis of adding FEC, the above effect was not improved and was still very poor.

[0234] In the electrolyte of Comparative Example 6, FEC and the compound of formula I are used. Compared with the comparative example 1 in which only FEC is used, although the capacity recovery rate after storage for 30 days at 60°C is improved, the DCR at minus 20°C, the DCR at 25°C, the DCR growth rate after storage for 30 days at 60°C, and the volume expansion rate after storage for 30 days at 60°C are all reduced; however, compared with Example 1, the DCR at minus 20°C, the DCR at 25°C, the DCR growth rate after storage for 30 days at 60°C, and the volume expansion rate after storage for 30 days at 60°C are still significantly higher, and the capacity recovery rate after storage for 30 days at 60°C is significantly poor.

[0235] Compared with Example 1, the electrolyte of Comparative Example 7 contains only the compound of Formula I and no compound of Formula II. Although the expansion rate of the fully charged negative electrode sheet after formation is also comparable, the capacity recovery rate and volume expansion rate of the lithium ion battery containing it at 60°C for 30 days are poor, and the DCR growth rate, DCR at -20°C and DCR at 25°C of the lithium ion battery at 60°C for 30 days are greatly deteriorated, and it is impossible to take both into account. Comparative Example 8 is similar to the above situation compared with Example 4 and cannot obtain excellent results.

[0236] Compared with Example 1, LiBOB was used to replace the compound of Formula II in Comparative Example 9. Although the expansion rate of the fully charged negative electrode sheet after formation was equivalent, the volume expansion rate of the lithium-ion battery stored at 60°C for 30 days, the capacity recovery rate stored at 60°C for 30 days, the DCR growth rate stored at 60°C for 30 days, the DCR at -20°C and the DCR at 25°C were greatly deteriorated. Similarly, compared with Example 4, LiBOB was used to replace the compound of Formula II in Comparative Example 10. Although the expansion rate of the fully charged negative electrode sheet after formation was equivalent, the volume expansion rate of the obtained lithium-ion battery stored at 60°C for 30 days was poor, and other effects were also significantly deteriorated.

[0237] Compared with Example 16, the electrolyte of Comparative Example 11 contains only the compound of Formula II and no compound of Formula I. The DCR at -20°C, the DCR at 25°C, the DCR growth rate at 60°C for 30 days and the capacity recovery rate at 60°C for 30 days of the obtained lithium ion battery are all deteriorated, and the volume expansion rate of the lithium ion battery stored at 60°C for 30 days is significantly deteriorated, and the expansion rate of the fully charged negative electrode sheet after formation is also poor.

[0238] Compared with Example 18, the electrolyte of Comparative Example 12 contains only the compound of Formula II and no compound of Formula I. The DCR at -20°C, the DCR at 25°C, the DCR growth rate at 60°C for 30 days and the capacity recovery rate at 60°C for 30 days of the obtained lithium ion battery are all deteriorated, and the volume expansion rate of the lithium ion battery stored at 60°C for 30 days is greatly increased, and the expansion rate of the fully charged negative electrode sheet after formation is also significantly deteriorated.

[0239] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that: The electrolyte comprises a 1,3-dioxocyclic compound and a polyboric acid compound; the structure of the 1,3-dioxocyclic compound is as shown in Formula I; the structure of the polyboric acid compound is as shown in Formula II-1 and / or Formula II-2; ; Wherein, in Formula I, n is selected from an integer within the range of 1 to 4; in Formula II-1 and Formula II-2, n2 is each independently selected from an integer within the range of 1 to 12; in Formula II-2, n3 is selected from an integer within the range of 1 to 3; R' in formula II-1 is selected from one or more of hydrogen, alkyl having 1 to 10 carbon atoms, cyclic alkyl, alkenyl, cyclic alkenyl, alkynyl, cyclic alkynyl, haloalkyl, haloalkenyl, haloalkynyl, aryl having 6 to 10 carbon atoms, and benzyl; M in formula II-2 is selected from one or more of Li, Be, Na, Mg, K, Ca, Mn, Fe, Co, Ni, Cu and Zn.

2. The electrolyte according to claim 1, characterized in that The 1,3-dioxocyclic compound is selected from one or more of compounds ac: 。 3. The electrolyte according to claim 1, characterized in that The polyboric acid compound is selected from one or more of the compounds dg: 。 4. The electrolyte according to claim 1, characterized in that The electrolyte satisfies one or more of the following conditions af: a. The content of the 1,3-dioxocyclic compound is 0.05% to 20%, where the percentage is the mass percentage of the electrolyte; b. The content of the polyboric acid compound is 0.05% to 6%, where the percentage is the mass percentage of the electrolyte; c. The mass ratio of the 1,3-dioxocyclic compound to the polyboric acid compound is (0.05-120): 1; d. The solvent in the electrolyte includes one or more of cyclic carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, trifluoroethyl methyl carbonate, trifluoropropylene carbonate, trifluoromethyl propylene, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; e. The additive in the electrolyte includes one or two of fluoroethylene carbonate and lithium bis(oxalatoborate); f. The lithium salt in the electrolyte includes one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

5. The electrolyte according to claim 4, characterized in that The electrolyte satisfies one or more of the following conditions ad: a. The content of the 1,3-dioxocyclic compound is 0.5% to 10%; b. The content of the polyboric acid compound is 0.5% to 6%; c. The mass ratio of the 1,3-dioxocyclic compound to the polyboric acid compound is (1-60): 1; d. The cyclic carbonate is ethylene carbonate and / or propylene carbonate.

6. The electrolyte according to claim 1, characterized in that The electrolyte comprises cyclic carbonate and fluoroethylene carbonate, and the electrolyte satisfies the following conditions: 1≤Y1 / (Y2+Y3)≤40; 0.05≤Y2 / Y3≤70; 0.1%≤Y1≤35%; 0.1%≤Y2≤35%; Wherein, the cyclic carbonate is ethylene carbonate and / or propylene carbonate, Y1 is the mass percentage of the cyclic carbonate in the electrolyte, Y2 is the mass percentage of the fluoroethylene carbonate in the electrolyte, and Y3 is the mass percentage of the 1,3-dioxocyclic compound in the electrolyte.

7. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to any one of claims 1 to 6.

8. The lithium ion battery according to claim 7, characterized in that The lithium-ion battery satisfies one or more of the following conditions ac: a. The positive electrode active material in the lithium-ion battery is one or more of a manganese-iron-lithium compound, an iron-lithium compound and a manganese-lithium compound; b. The content of manganese in the positive electrode active material of the lithium ion battery is greater than 10%, where the percentage is the molar ratio of the total molar number of metal elements other than lithium in the positive electrode active material; c. The negative electrode active material in the lithium-ion battery is selected from graphite and / or silicon materials.

9. The lithium ion battery according to claim 7, characterized in that The negative electrode active material in the lithium ion battery includes a silicon material, the electrolyte includes fluoroethylene carbonate, and the electrolyte meets the following conditions: 0.1≤(Y2+Y3) / Z1≤1; 0.1%≤Z1≤30%; 0.1%≤Y2≤30%; Wherein, Z1 is the mass percentage of the silicon material in the negative electrode active material; Y2 is the mass percentage of the fluoroethylene carbonate in the electrolyte; and Y3 is the mass percentage of the 1,3-dioxocyclic compound in the electrolyte.

10. An electronic device, characterized in that: It comprises a lithium ion battery as claimed in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Lithium ion secondary battery and electrolyte thereof

    CN104979586A

  • Lithium-ion battery and electrolyte thereof

    CN105336984A

  • Electrolyte and lithium ion battery containing same

    CN110943250A

  • Electrolyte and electrochemical device

    CN111525191A

  • Additive for lithium ion battery, lithium ion battery and electric equipment

    CN115863764A